Experimental investigation of face instability for tunnels in sandy cobble strata - Qiguang Di; Pengfei Li; Mingju Zhang; Xiaopu Cui (Underground Space, 2023)
In order to investigate the influence of face instability for tunnels with different burial depths in sandy cobble strata on earth pressure and the instability region, geomechanical model tests and numerical simulations were performed. The continuous excavation method was adopted to reduce the pressure of the soil bin and restore the real engineering situation. Earth pressure in three directions of the observation section in front of the tunnel face was monitored during the tunneling of the shield. Evolutions of the lateral stress ratios at different stages were also investigated. The instability area of the shield tunnel face in sandy cobble strata with different burial depth ratios during the instability stage was obtained based on the change ratio of earth pressure and compared with existing researches. The earth pressure began to change when the excavation was one shield diameter away from the observation section, and when the excavation reached the observation section, the earth pressure decreased significantly. The burial depth of shield tunnel in the sandy cobble strata has a significant impact on the evolution of soil arch and the size of the failure area. The numerical simulation of the continuum medium cannot reflect the stress redistribution characteristics of the granular body like sandy cobble strata, and the failure area or stress disturbance area obtained by the model test is larger than the numerical simulation result. Existing methods have deviations in analyzing the failure area of shield tunnel face in sandy cobble strata. It provides not only guidance for shield tunnel excavation engineering in sandy cobble strata, but also a reference for the theoretical research on failure areas.